CHALCHOGENIDE INDUCED INTRAMOLECULAR INTERACTIONS IN [2.2]PARACYCLOPHANES: A REVIEW - SÂRBU, Laura Gabriela; BAHRIN, Lucian Gabriel; HOPF, Henning; BÎRSĂ, Mihail-Lucian (Studia Universitatis Babeș-Bolyai Chemia, 2019)
The intramolecular interactions in pseudo-geminally substituted [2.2] paracyclophanes induced by chalchogenide halides is reviewed. The subtitution reactions with sulfur dichloride and disulfur dichloride and the addition reactions of selenium dihalides and diselenium dichlorides are highlighted.